A Study of Ethical Dilemmas and Regulation of AI Chatbots - Song, Xiaokang (Journal of Theory and Practice of Social Science, 2023)
Chatbots are the product of the development of artificial intelligence to a certain stage, and have different degrees of technical effects under the iteration of technology. Under the development of media technology in recent years, the artificial intelligence robot represented by Chatgpt has attracted widespread attention because of its ability to learn dialogue, and from the current stage of development, there is no doubt that intelligent chatbots have brought about a worldwide revolution in communication technology. It has had a great impact on various fields such as sociology, communication, computation, education, etc. It has produced an underlying reaction to various fields from the technical architecture, changed the previous way of creating, interacting, educating and other behaviours, and has also had an important impact on social construction and interaction. Its unique way of knowledge learning and updating not only brings new possibilities to the network communication ecology, but also brings some ethical dilemmas in communication, which require people to be alert to this new technology and take corresponding preventive and regulatory measures.